The Representation of Taste and Social Class of Del Monte Barbeque Sauce Advertisement - Yazid Rukmayadi; Puspa Safitrie; Purnama Rika Perdana; Ilzamudin Ilzamudin; Undi Siti Sutiawati (English Education, Linguistics, and Literature Journal, 2022)
This study aims to describe how taste and social class are represented through language signs, both verbal and non-verbal signs, in Del Monte Barbeque Sauce advertisement. In analysing this advertisement, Barthes' semiotic theory and Bourdieu's concept of taste and social class are used. The method used in this study is descriptive analysis. Based on the results of the analysis, it is found that this advertisement aims to convince readers to be able to bring the feel of luxury, which is identical to upper class, at home through the products offered. This departs from the advertiser's assumption that basically people from the working class, which is the segmentation of the readers of this ad, have the same taste for goods as people from the upper class.